Unveiling the University Students’ Energy Saving Intention Using a Norm Activation Model - Ling, Liing-Sing; Ling, Pick-Soon (International Journal of Energy Economics and Policy, 2025)
The increase in energy demand due to excessive energy consumption and also the consequences of traditional energy generation toward the society and environment have been a global problem that requires immediate action. Besides diversifying the energy sources to renewable energy, reducing energy consumption is also perceived as one of the effective strategies to overcome this issue. Energy conservation or more precisely energy-saving behaviour could alleviate these problems. Empirically, numerous studies have been conducted and offer extensive evidence in this subject area. However, studies that exclusively focus on university students in the university setting are scarce. Moreover, the evidence in the literature has not achieved a consensus regarding the factors that affect a personal’s energy-saving behaviours. With that, the objective of the study is to investigate the factors that affect university students’ energy-saving behavioural intentions and also to investigate the mediating effect of personal norms (PN) and attitudes (ATT) on their energy-saving behavioural intentions. Through purposive sampling, the responses from 200 university students were gathered and the results from the partial least square-structure equation modelling (PLS-SEM) found that the energy-saving intention of the university students is significantly affected by both PN and ATT. Besides, ascription of responsibility (AR) and awareness of consequences (AC) have substantial effects on PN, while energy-saving knowledge (ESK) and environmental knowledge (EK) also demonstrated significant influence on ATT. Additionally, the study also found that both PN and ATT could be effective mediators in mediating the indirect influence of AR, AC, ESK, and EK on ESI. These findings offer crucial implications as they further enrich the existing knowledge in the subject area and they also provide important references for stakeholders in formulating effective strategies that would further nurture the individual’s energy-saving behaviour.